Advances in Image and Graphics Technologies : 10th Chinese Conference, IGTA 2015, Beijing, China, June 19-20, 2015, Proceedings - Tan, Tieniu; Ruan, Qiuqi; Wang, Shengjin; Ma, Huimin; Di, Kaichang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 10th Chinese Conference on Advances in Image and Graphics Technologies, IGTA 2015, held in Beijing, China, in June 2015. The 50 papers presented were carefully reviewed and selected from 138 submissions. They provide a forum for sharing new aspects of the progresses in the areas of image processing technology, image analysis und understanding, computer vision and pattern recognition, big data mining, computer graphics and VR, image technology application.
Image processing technology -- Image analysis und understanding -- Computer vision and pattern recognition -- Big data mining -- Computer graphics and VR -- Image technology application.
Keywords: Computer vision; Optical pattern recognition; Artificial intelligence; Computer graphics; Image Processing and Computer Vision; Pattern Recognition; Artificial Intelligence; Computer Graphics